Pengendapan Unsur Tanah Jarang Hasil Digesti Monasit Bangka Menggunakan Asam Sulfat - Anggraini, Mutia; Sumarni, Sumarni; Sumiarti, Sumiarti; Rusyidi, Rusyidi; Waluyo, Sugeng (BRIN Publishing, 2012)
Rare earth elements are elements that widely used in many products. Rare earth elements nature are not found in a free state, but they are in the complex compounds, so that chemically processing is required to separate the Rare earth elements from their complex compounds. Monazite as by product of Bangka tin process contains several major elements, such as 0.298% uranium (U), 4.171% thorium (Th), 23.712% phosphat (P2O5) and 58.97% rare earth elements (REE) oxide. These elements can be individually separated through a process of precipitation stages. The separation process used in the study is the method of acid by using sulfat acid as reagen and filtrat digestion as feeds. The process of digestion dissolve the elements U, Th, RE and phosphate from the complex compound. Rare earth elements that are disolved can be separated from the complex compounds by using sulfat acid precipitation process. The objective of research is to set the optimal conditions for the Rare earth elements precipitation with sulfat acid. The result showed that the amount of sulphuric H2SO4 which added is 3.5 times volume of feed and precipitation time is 20 minutes, percentage of precipitation recovery is 61.21 % REE, 78.46 % U, and 93.56 % PO4.